How Job Satisfaction Moderates the Determinant Factors of Managerial Performances at PT PLN (Persero) UIP3B Sumatera - Ismaida, Putri; BZ, Fazli Syam; Yusmita, Fifi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Achieving optimal performance necessitates precise goal setting, and access to quality information to enhance the clarity and effectiveness of these goals. Therefore, the variables used in this research are considered capable of affecting managerial performance, which in turn impacts company profits. This study aims to examine the effect of independent variables on the dependent variable with the inclusion of a moderating variable. This study uses a qualitative method that conducts a census of 64 research populations consisting of structural and staff as correspondents to answer questionnaires that use a Likert scale. This study found that participatory budgeting, job-relevant information, and clarity of budget targets all significantly impact managerial performance, both simultaneously, and individually. However, Participatory budgeting and job-specific information have a direct impact on managerial performance, whereas the clarity of budget goals doesn't. Furthermore, job satisfaction enhances the influence of participatory budgeting, job-specific information, and clear budget goals on managerial performance. This study aims to benefit companies and guide future research.